Nutritional status and body composition of inpatients: the effects of nutritional transition - Kátia Cristina Portero-McLellan; Júlia Laura Delbue Bernardi; Patricia Jacob; Cristiane Stelato Rocha Soares; Patrícia Baston Frenhani; Vânia Aparecida Leandro Mehri (Universidade de Fortaleza, 2010)
Objectives: To investigate the effects of nutritional transition on the nutritional status and body composition of inpatients. Methods: We assessed 819 inpatients (435 men and 384women) regarding clinical, anthropometric and dietary aspects. The anthropometric variables studied were: current weight (CW), height (H), waist circumference (WC), hip circumference (HC), arm circumference (AC), triceps skinfold (TSF) and subscapular skinfold thickness (SST). From these measures were determined: the body mass index (BMI), the waist and hip ratio (WHR), the waist and height ratio (RCA), the arm muscle circumference (AMC), the arm muscle area (AMA) and arm fat area (AFA). For the diagnosis of central adiposity, we used the relationship between waist and hip circumferences. Results: The mean age was 53.7 ± 16.0 years, with hospital stay of 8 days, being higher among the elderly (p <0.01). Most patients (47.8%) were overweight or obese, 48.6% presented altered values of waist circumference and 76.4% had central adiposity. Cardiovascular disease accounted for 45.4% of total admissions, and 60.4% among the elderly. Conclusion: This study showed high prevalence of obesity and central adiposity among inpatients regardless of gender, age, and the reason for admission, evidencing the effects of nutritional transition in the studied population.